Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.20884/1.bioe.2021.3.3.4224
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Penelitian ini bertujuan untuk mengetahui jenis cacing, prevalensi dan intensitas telur cacing gastrointestinal pada kambing yang dipelihara secara intensif dan semi intensif, serta mengetahui perbandingan prevalensi dan intensitas cacing gastrointestinal berdasarkan jenis kelamin dan usia kambing. Penelitian ini dilakukan pada peternakan kambing intensif dan semi intensif di Desa Klareyan, kecamatan Petarukan, Pemalang dengan metode survey purposive random sampling pada bulan November 2020. Jenis cacing gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…A study conducted by Khirqah et al (2021) showed that the prevalence of goats with helminth infestation in intensive rearing was 90% and 100% in semi-intensive rearing.…”
Section: Helminths Eggs In Feces Resultsmentioning
confidence: 99%
“…A study conducted by Khirqah et al (2021) showed that the prevalence of goats with helminth infestation in intensive rearing was 90% and 100% in semi-intensive rearing.…”
Section: Helminths Eggs In Feces Resultsmentioning
confidence: 99%